The Relationship between Self Control and Premarital Sexual Behavior among Emerging Adults - Khairatus Sakinah; Yarmis Syukur (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aimed to examine the relationship between self-control and premarital sexual behavior among emerging adults. The research employed a quantitative approach with a descriptive correlational design. The population consisted of all undergraduate students from Faculty X at University Y who were enrolled between 2018 and 2024 and remained actively registered during the January–June 2025 semester. A total of 370 respondents were selected using a proportional random sampling technique. Data were collected through a self-control questionnaire and a premarital sexual behavior questionnaire. The data were analyzed using descriptive statistical techniques and Spearman’s rho correlation analysis with the assistance of SPSS for Windows 20.0. The findings revealed that the level of self-control among respondents was categorized as moderate (49.46%), while premarital sexual behavior was also categorized as moderate (32%). Furthermore, the results indicated a statistically significant positive correlation between self-control and premarital sexual behavior among emerging adults, with a correlation coefficient of 0.456 and a significance level of 0.000, indicating a moderate relationship. The findings imply the importance of guidance and counseling services, including individual counseling, information services, group guidance, and group counseling, in supporting emerging adults. Such interventions may help students strengthen their self-control and avoid engagement in premarital sexual behavior.